2011
DOI: 10.19030/iber.v4i9.3617
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation Asian-Indian Reactions To Asian-Indian And American Magazine Advertisements

Abstract: This paper is an extension of a previous study which addressed cultural perceptions of first generation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Specifically looking at CSA, a study conducted in Great Britain found that disclosure of CSA among South Asian women was often impeded by lack of basic knowledge of CSA; lack of awareness surrounding the existence of the CSA services; fear of public exposure due to disclosure of CSA; fear of culturally insensitive responses from professionals; and other cultural factors such as izzat [honor/respect], haya [modesty], and sharam [shame/embarrassment]) [19,20]. Furthermore, previous research has found that the upbringing and personality of Asian Indians are partly shaped by the influence of extended adult family members, and they are expected to depend on their parents, grandparents, other siblings, and aunts and uncles throughout their lifespan [21]. This familial norm is often a significant barrier for disclosure of family violence and CSA within families [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically looking at CSA, a study conducted in Great Britain found that disclosure of CSA among South Asian women was often impeded by lack of basic knowledge of CSA; lack of awareness surrounding the existence of the CSA services; fear of public exposure due to disclosure of CSA; fear of culturally insensitive responses from professionals; and other cultural factors such as izzat [honor/respect], haya [modesty], and sharam [shame/embarrassment]) [19,20]. Furthermore, previous research has found that the upbringing and personality of Asian Indians are partly shaped by the influence of extended adult family members, and they are expected to depend on their parents, grandparents, other siblings, and aunts and uncles throughout their lifespan [21]. This familial norm is often a significant barrier for disclosure of family violence and CSA within families [5,6].…”
Section: Introductionmentioning
confidence: 99%